Proyecto para la reestructuración de procesos administrativos de dipaso s.a. (importador y distribuidor mayorista y minorista de cosméticos, productos de bazar y consumo masivo) - Parra Solis, Stephanie Vanessa (2009)
DIPASO is an importer and nationwide distributor of bazaar items, cosmetics and personal care. Given the growth that has been taking place at the Business Group, management believes that it is necessary to lead a reengineering on internal processes. Given the competition in the market, it is a commitment to the company and its collaborators at the forefront to start changes in technology and processes as it relates to this growth is not steady but only lasts in the long run. This also is intended to produce competitive advantages which will result ultimately in increased sales. For the above change should first know the reality of DIPASO, it will be known through the investigations carried out to external customers, internal customers and suppliers. This study will allow correct consensus decision making for administrative restructuring and thus bolster the competitive advantage that has been providing to the Ecuadorian market, which is expected to increase in overall sales and positioning as a provider of personal care, bazaar products and cosmetics.